Antioxidant potential of peel off facial mask with ethanolic extract of Cochlospermum regium (Revista Brasileira Multidisciplinar, 2025)
The present work is dedicated to developing a peel-off facial mask formulation with ethanolic extract from the leaves of Cochlospermum regium (Schrank) Pilger, as well as evaluating its antioxidant activity and comparing it with a commercial mask. A peel-off facial mask base containing the ethanolic extract of C. regium leaves was prepared and tested for its stability and antioxidant potential. The antioxidant activity was investigated through the mechanism of 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and compared with a commercially available facial mask marketed as an antioxidant product. The C. regium peel-off mask exhibited good viscosity, spreadability, color, odor, and film formation. In terms of antioxidant activity, the formulation showed an IC50 of 5.10, close to that of the control, ascorbic acid, whereas the commercial facial mask did not demonstrate the advertised activity (IC50 > 250). The results are novel and promising for the use of C. regium extracts in cosmetic products, as the developed formulation allows for easy application and removal, in addition to excellent antioxidant activity that may help prevent or reduce skin disorders associated with oxidative stress.
Keywords: Cochlospermum regium; natural cosmetics; face masks; antioxidants.